A passage to Tokyo: The art of Ozu, remembered. Issue 1 (1st April 2013) - Cardullo, Robert
The most appropriate analogy for the art in Yasujiro Ozu's films – particularly Tokyo Story (1953), the subject of this article – is Zen Buddhism, as it is for traditional Japanese arts, crafts or skills such as painting, gardening, archery, the tea ceremony, haiku poetry, Noh drama, judo and kendo. Zen is not an organized religion with social and political concerns like Shintoism (itself devoted in part to nature worship, to the cultivation of a harmonious relationship between man and the natural environment) or Christianity, but a way of living that has permeated the fabric of Japanese culture for well over 1300 years. The fountainhead of Zen is a fundamental unity of experience in which there is no dichotomy or discord between man and nature (in western terms, this comes close to pantheism), and which thus permits the attainment of transcendental enlightenment through meditation, self-contemplation and intuitive knowledge. The great threat to this communal oneness, it could be argued, has been 'modernization' in the wake of the industrial-technological revolution, especially as such modernization affected Japan during the post-World War II period: precisely the period during which Tokyo Story takes place, and which forms a quiet but nonetheless meaningful backdrop for its action.